Leveraging small and medium-sized enterprise finance through value chains in Georgia - Giorgi Khishtovani; Mariam Saghareishvili; Sopho Basilidze (Asian Development Bank Institute (ADBI), 2019)
A strong small and medium-sized enterprise (SME) sector can contribute much to a country's economy by fostering innovation, creating jobs, and reducing poverty. This paper examines the status of SME finance in Georgia and the involvement of Georgian SMEs in global value chains. The role of SMEs in Georgia's economy, SME funding, and the status of financial inclusion for SMEs are analyzed. Moreover, the level of financial literacy and skills of SME entrepreneurs is discussed. Furthermore, the paper analyzes the Georgian agricultural sector's value chain and the involvement of this sector in global value chains by discussing the case study of the hazelnut. An analysis of the agricultural sector's value chain financing in Georgia is carried out, its availability and development are discussed, and best practices of value chain financing are analyzed. Based on existing information, the paper identifies barriers to SME finance in Georgia and proposes policy recommendations and immediate actions with regard to existing government policies.
Keywords: D53; G23; L26; Q13; Q14; Q17; 330; SME sector; financial literacy; financing; global value chain; value chain financing; agriculture